2019
DOI: 10.1080/13803395.2019.1586840
|View full text |Cite
|
Sign up to set email alerts
|

Smell your memories: Positive effect of odor exposure on recent and remote autobiographical memories in Alzheimer’s disease

Abstract: Introduction: There is a burgeoning interest in the effects of odor exposure on autobiographical memory in Alzheimer's disease (AD). We pursued this line of research by assessing the effect of odor exposure on the retrieval of recent and remote memories in AD. Method: Twenty-six patients with mild AD and 28 controls were tested in two conditions: with and without odor exposure. In each condition, participants were invited to retrieve two childhood memories, two adulthood memories, and two recent memories. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…In the present study, our goal was to determine the most relevant cue for AM retrieval in patients with early to mild AD, comparing odors, sounds and pictures. In line with the work of Glachet and col-191 leagues (i.e., [53][54][55][56]), we suggest that odors may [69], productive language with a verbal fluency task [70], episodic memory with the 5-word test [71], and attention and working memory with the forward and backward digit spans [72].…”
Section: Introduction 30supporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, our goal was to determine the most relevant cue for AM retrieval in patients with early to mild AD, comparing odors, sounds and pictures. In line with the work of Glachet and col-191 leagues (i.e., [53][54][55][56]), we suggest that odors may [69], productive language with a verbal fluency task [70], episodic memory with the 5-word test [71], and attention and working memory with the forward and backward digit spans [72].…”
Section: Introduction 30supporting
confidence: 83%
“…For example, the "imageability" of a verbal cue was found to influence the age, specificity, and vividness of AMs [41][42][43][44]. There is also support for the notion that visual dominance could influ- The effect of odors on AM retrieval in AD has recently been a key research topic for Glachet and colleagues [53][54][55][56]. Results from this line of research showed various advantages in exposing AD patients to odors before retrieving AMs, when comparing to the absence of sensory exposition.…”
Section: Introduction 30mentioning
confidence: 99%
“…The study included 25 participants at the mild stage of AD and 23 healthy elderly adults. The sample size is similar to previous studies [2,21,46] using a close experimental design, and was sufficient to observe significant differences between AD and control participants in both experimental conditions (odor and odor-free). From the original sample of 36 AD participants, six participants were excluded from the study due to olfactory impairment, seven due to the very low scores on the cognitive battery, and one due to inability to follow the instructions provided.…”
Section: Methodsmentioning
confidence: 56%
“…They did not find significant effect of odor in terms of specificity and reminiscence in healthy people, suggesting that this type of cueing is particularly efficient when autobiographical memory is impaired. The team of Dr. Glachet [162] also found a positive effect of odor exposure on recent autobiographical memories in AD. Additionally, Glachet & El Haj [161] investigated emotional characteristics (arousal and valence) and subjective reliving of odor-evoked autobiographical memories in AD.…”
Section: Emotional Sensorial Stimulations and Self-consciousness In Amentioning
confidence: 93%
“…To our knowledge, only five studies have examined the impact of odor on autobiographical remembering in AD [123,[160][161][162][163]. All studies have demonstrated the positive effects of odor on personal event memories.…”
Section: Emotional Sensorial Stimulations and Self-consciousness In Amentioning
confidence: 99%